Ed Kemper [videorecording (Blu-Ray)] : the true story of an American psycho - Billings,Jeff; Leblanc, Shon; Castro, Joe; Castro, Joe; Ferif, Jahad; Band, Richard, 1953-; Muscal, Michael; Johnston, Stephen (Stephen D.); Priver, Susan; Priver, Susan; Irons, Jerry; Decker, Jeffrey; et al. (Epic Pictures, 2025)
"The horrifying true story of Ed Kemper, a cunning and sadistic serial killer shaped by childhood abuse, whose charm masked his grotesque obsession with murder, mutiliation, and the ultimate act of revenge on his mother." --